The impacts of organisational justice and psychological resilience on employee commitment to change in an M&A context. (29th July 2017) - Cho, Insu; Park, Heejun; Dahlgaard-Park, Su Mi
Abstract : Many firms have carried out organisational change, such as mergers and acquisitions, to adapt to the rapidly changing business environment. During such changes, it is crucial for firms to provide an environment that will enhance employees' psychological stability and commitment to change. Therefore, this study explores factors that increase employee commitment to change during mergers and acquisitions and identifies the process that forms commitment to change. To achieve the research goals, the study uses conservation of resources theory to extract factors that may influence employees' commitment to change: three types of organisational justice are extracted as an organisational resource and psychological resilience (PR) is extracted as an individual resource. The study also applies psychological contract theory to extract mediators that link resources and employee commitment to change during the merger and acquisition process. The study empirically examines the research model using a structural equation model, based on 222 respondents who experienced mergers and acquisitions in South Korea. The three types of organisational justice and PR have positive relationships with affective commitment to change through the relational contract. Interactional justice, one type of organisational justice, and PR have negative relationships with continuance commitment to change through the transactional contract. This study may call human resource managers' attention to the importance of employees' psychological stability and may suggest possible ways to increase employees' affective commitment to change in situations where there are frequent changes, such as mergers and acquisitions.